Penyeragaman Rasm Mushaf Cetak dan Senjakala Rasm Qiyasiy - Abdul Hakim; Hasbullah Diman (SUHUF, 2025)
This article reviews Ganim Qadduri’s book Tawhid al-Rasm wa al-Dabt fi Tibaʿat al-Masahif, which addresses the standardization of rasm and dabt in Qurʾanic manuscripts (masahif). The study is situated within the extensive historical context of rasm variations in Qurʾanic codices, encompassing both rasm ʿusmani and rasm qiyasi (imlaʾi), which have evolved from the manuscript tradition to the era of print. This article demonstrates that variations in rasm constitute a historical reality originating from differences in the Companions’ codices, divergent scholarly transmissions (riwayat) of rasm, and preferential choices (tarjih) within the scholarly tradition. Qadduri emphasizes the urgency of unifying rasm and dabt to ensure consistency in printed Qurʾanic texts, enhance readability, and preserve the integrity of recitation. He proposes several methodological approaches to standardization, including reliance on authentic early manuscripts, the selection of a single scholarly transmission of rasm, the designation of authoritative scholars’ codices as reference texts, or the establishment of collective decisions through scholarly committees (lajnah ʿilmiyyah). This study concludes that the global standardization of rasm and dabt in printed Qurʾanic texts represents a feasible agenda through collaborative efforts among Qurʾanic revision committees across the Islamic world. Nevertheless, such an endeavor requires methodological clarity, consistency in reference frameworks, and broad cross-denominational and transnational consensus.